2021
DOI: 10.3390/molecules26195908
|View full text |Cite
|
Sign up to set email alerts
|

White Chocolate with Resistant Starch: Impact on Physical Properties, Dietary Fiber Content and Sensory Characteristics

Abstract: Resistant starch (RS) is a part of insoluble dietary fiber, and it could be recognized as a functional food ingredient in some types of confectionery products that lack dietary fiber. Unlike dark and milk chocolate, white chocolate does not contain fat-free cocoa solids rich in dietary fiber. In the present study, 5%, 10%, and 15% of white chocolate were substituted with RS in order to improve the nutritional value of enriched white chocolate. The influence of RS on rheological, textural, and thermal propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the present study, IGs with different structural properties showed dissimilar fermentation behavior; for example, they were fermented to different degrees almost throughout fermentation, and a higher degree was seen with BG, L, and BY, which have high solubility or simple structures [56][57][58], when compared with PAC, R, and Lit, which are insoluble or have complicated structures [59][60][61]. Such a result was expected, and has been evidenced in fructo-oligosaccharides varying in solubility [62]; additionally, polysaccharides differed in branching degree, since a complex structure needs the cooperation of various enzymes for a complete breakdown, and most enzymes prefer a soluble substrate.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, IGs with different structural properties showed dissimilar fermentation behavior; for example, they were fermented to different degrees almost throughout fermentation, and a higher degree was seen with BG, L, and BY, which have high solubility or simple structures [56][57][58], when compared with PAC, R, and Lit, which are insoluble or have complicated structures [59][60][61]. Such a result was expected, and has been evidenced in fructo-oligosaccharides varying in solubility [62]; additionally, polysaccharides differed in branching degree, since a complex structure needs the cooperation of various enzymes for a complete breakdown, and most enzymes prefer a soluble substrate.…”
Section: Discussionmentioning
confidence: 60%
“…In this regard, the higher amounts of grape seed oils resulting from higher levels of GPP addition might cause problems in the tempering process and in the uniform crystallisation of cocoa butter due to the changes in the fat levels and fat composition, which negatively affected the hardness values, and stability and acceptability of white chocolates. Unlike the GPP20 and GPP30 samples, an increase in the hardness value of GPP10 group can be attributed to the more rigid and complex structure resulting from increasing amounts of fibre content without negatively affecting the fat content and crystallisation of chocolate samples (Lončarević et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 8% and 10% of B to white chocolate significantly (p < 0.05) increased the content of total dietary fiber in both enriched chocolates; however, there was no significant difference between the values in fortified chocolates (1.38% in C-B8 and 1.48% in C-B10). However, research conducted by our team [44] showed that the dietary fiber content in white chocolate could be increased up to 9.76% using 15% of resistant starch in the raw composition of white chocolate. Both amounts of B significantly (p < 0.05) reduced the values of carbohydrates, where C-B8 had significantly (p < 0.05) lower value (53.26%).…”
Section: The Impact Of Encapsulates On the Chemical Composition Of Ch...mentioning
confidence: 95%